Os jogos escolares brasileiros chegam ao século XXI: reprodução ou modernização na política de esporte escolar? - Kiouranis, Taiza Daniela Seron (Universidade Federal do Paraná, 2017)
The Brazilian School Games (JEBs) are a competitive sports event held since 1969. Throughout its history, JEBs have been redesigned and managed by different government agencies and institutions. Since 2005, the Brazilian Olympic Committee (COB) has become the main organizer, with the support of the Ministry of Sport (ME) and Globo Organizations (OG). This new scenario pointed to a possible modernization of these events. Considering this new phase, we established as a central objective of this study: to analyze the development of the Brazilian School Games in the period between 2005 and 2014, from the point of view of its organizational model and the dynamics of agents, institutions and structures involved. In order to meet the proposed objective, the present study is a qualitative and quantitative research, with data from documents (JEBs’ General Regulations, official final results bulletins, journal published by the COB) and interviews (two agents from ME and one from COB). In order to analyze the data, we take advantage of studies that discuss the field of sport in the contemporary world, as well as the theoretical-methodological assumptions of Pierre Bourdieu and his Theory of Fields. From the results of this research, it is noted that the JEBs in the period from 2005 to 2014 presented several symptoms of modernization, such as the guarantee of financing; The expansion of the number of students and schools attended; The increase in the number of modalities; The modernization of facilities, both in terms of sports competition, and in terms of hosting delegations; The international projection of the event, of students and teachers involved; The technical and standardized requirement, taking care of the regulatory institutions; The insertion of activities that address broader global themes such as sustainability; And the presence of the media in the placement of the JEBs and the consequent opening for the entry of sponsors. However, we noticed that sports performance remained a legitimating background, sustaining the old belief of school sport as the "redeemer" of Brazilian sport. In the agent discourse there is a strong tendency towards the idea of sports talent and the formation of a base for the top of the high income, a fact that points to a subfield dominated by the field of sports. Thus, these events have been configured by the reproduction of models of the sport of yield, demonstrating a reproduction of structures of power. Thus, the work progresses in the sense that the JEBs between 2005 and 2014 transition between modernization and reproduction, a "conservative modernization" or a "modernized reproduction".